Control of process of building geometry design/Pastatų geometrijos projektavimo proceso valdymas - Čiupaila, Lionginas; Žiūrienė, Ryte (Journal of Civil Engineering and Management, 2001)
Methods of the modern building design do not only help designers in their work, but also raise a number of different questions, especially in the cases of using maximum computer possibilities. One of the possible ways is to create a model of the interface of a workstation, which would have the following properties:– The design process (design tools and information) has to be made automatically, depending on the type of the designed object.– There should be a possibility to gain automatically one's experience and to use the existing information. – The way of the automatic control of the digital information has to be evaluated, as well as the means of the maximum use of the automatic information control qualities should be estimated.The controlling of the information becomes rational only by the use of intelligent systems (Fig 1). This investigation covers the problems related with a spatial modelling only (Fig 2). Basic systems could not be rational due to their general purpose (Fig 3), so it is necessary to create a structure of separate groups of problems (Fig 4). The course and the means of solving this problem depend on the way one chooses: the design according to the analogue (Fig 5) or the design of an entirely new object (Fig 6). The rational work could be possible only by making the means of modelling and control (Fig 7–9). General conclusions: 1. While analysing the methods of computer design used in Lithuanian companies of architectural design, there has been determined: a) In the design process computers are being used as simple drawing tools for making different operations like with a pencil, to depict separate lines or even points. Computers are not used as functional objects, which realisation has become possible by using modern means of computer; b) integration of computer design is used only in the limits of one project on rudimental level. 2. The analysis of the mostly used computer aided design (CAD) systems shows: a) the most common and specialised CAD systems are used which differ in their possibilities and commercial price; b) in spite of the existing technical and programme conditions, the highest achievement is only the development of integration with very low intelligent possibilities. 3. The interface of the visualisation of building spatial solution has been prepared on the base of analysis and created intellectual models: a) the main functions of spatial design interface have been discussed, as well as algorithms of their realisation have been prepared; b) a scheme of tool structure has been made. 4. By using the proposed models and algorithms there have been created the fragments of programme, which are realised by solving an example. This material could be used in the educational and practical design process. The algorithms of main operations and programmed models are made, enabling the use of modern design technologies and projects, created in traditional way.Article in Lithuanian.First Published Online: 30 Jul 2012